1993
DOI: 10.1007/bf02244946
|View full text |Cite
|
Sign up to set email alerts
|

Subjective, behavioral and physiological responses to intravenous meperidine in healthy volunteers

Abstract: Meperidine is a mu opiate agonist that is frequently used to treat pain. We examined in healthy volunteers (N = 10) the effects of intravenous meperidine (0, 0.25, 0.5, and 1.0 mg/kg) on mood and psychomotor performance. A randomized, placebo-controlled, crossover design was used in which subjects were injected with meperidine or saline in a double-blind fashion. Subjects completed several subjective effects questionnaires commonly used in abuse liability testing studies before drug injection and at periodic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 40 publications
6
28
0
Order By: Relevance
“…In addition to opioid-induced gut side effects, opioid-induced unpleasant feelings, such as dizziness, headache, nausea, dry mouth, warmth, tingling, and itchiness, have long been recognized (Lasagna et al, 1955). In humans, the effects of drugs on subjective responses could be expressed in quantitative terms Beecher, 1959, 1962;Fraser et al, 1961;Zacny et al, 1994). In this study, using the modified adjective checklist, which is sensitive to the subjective and somatic effects of -class opioid agonists (Preston et al, 1989), we observed that subcutaneous methylnaltrexone significantly reduced the overall subjective effect rating.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…In addition to opioid-induced gut side effects, opioid-induced unpleasant feelings, such as dizziness, headache, nausea, dry mouth, warmth, tingling, and itchiness, have long been recognized (Lasagna et al, 1955). In humans, the effects of drugs on subjective responses could be expressed in quantitative terms Beecher, 1959, 1962;Fraser et al, 1961;Zacny et al, 1994). In this study, using the modified adjective checklist, which is sensitive to the subjective and somatic effects of -class opioid agonists (Preston et al, 1989), we observed that subcutaneous methylnaltrexone significantly reduced the overall subjective effect rating.…”
Section: Discussionsupporting
confidence: 46%
“…A modified opiate adjective checklist reflecting opioid agonist effects was used (Fraser et al, 1961;Zacny et al, 1994;Yuan et al, 1998). This list consisted of 12 items: "flushing", "stimulated", "numb", "drunken", "difficulty in concentrating", "drowsy (sleepy)", "coasting or spaced out", "turning of stomach", "skin itch", "dry mouth", "dizzy", and "nauseous".…”
Section: Methodssupporting
confidence: 42%
“…Although exophoria was not increased by oxycodone in the time-course analysis, the peak rating of exophoria was higher in the 30-mg oxycodone condition relative to the placebo condition. Thus, oxycodone produces effects that resemble those of other mu-opioid agonists that have been tested in this laboratory as well as others with this particular population (for instance: Zacny et al 1992Zacny et al , 1993Petry et al 1998;Black et al 1999;Walker and Zacny 1999;Hill and Zacny 2000). In addition, oxycodone in this study tended to produce a similar spectrum of effects as did morphine.…”
Section: Discussionmentioning
confidence: 43%
“…These effects appear to be more severe in patients receiving higher doses of opioids or agonist/antagonist opioids as compared to pure agonists, in patients treated with other psychoactive drugs, and in those with borderline cognitive failure (44). In most patients, the cognitive failure is more like the 'slowing down' of cognitive function, than an increase in both the number of errors or major errors in judgement (44).…”
Section: Cogniti6e Failure and Sedationsupporting
confidence: 38%